Effect of Tackifier Addition on Cushion Compound Formulation for Tire Retreading Application - Lies Agustine Wisojodharmo; Dewi Kusuma Arti; Retna Deca Pravitasari; Ade Sholeh Hidayat; Aisyah I. Nisa; Muhammad N. Ariesta (Research Center for Chemistry - LIPI, 2020)
Tire retreading is a prospective industry. Old tires are repaired and retreaded with suitable tread compounds to fulfill the requirement as the new ones. One of the important components in tire retreading process is cushion compound. Cushion compound consists of unsaturated rubber, in this case natural rubber Hevea brasiliensis was used, less phr of filler compared to the retread compound, and additives such as peptizer, tackifier, processing oil, antioxidant, activator, accelerator and curatives. Tackifier is an important component in cushion compound since its role to make a bonding between different layer, the initial tire after buffing and new retread layer. Tackifier should has good resistance, good compatibility and does not affect the rheological and dynamical properties of bonded rubber. The general tackifier that used in industries are hexamethyl tetramine as methylene donor and resorcinol as methylene acceptor. There is certain reaction between those two additives that determine how good the performance of cushion compound and its effect to retreading process. To obtain optimum reaction, comparison between resorcinol and hexamethyl tetramine were varied as 1:1 (FRR1), 1:2 (FRR2) and 1:3 (FRR3). Hardness test, compression test, rebound resilience, tensile and tear strength, and FTIR were done to observe the optimum variation for retread application. Compared to the control with no tackifier at all, FRR2 showed the optimum result with 21.75 MPa (min. 19 Mpa) and 454,54% elongation at break (min. 450%). The most interesting result was observation by using FTIR, it was detected that the crosslink density was significantly higher than other formulation. It is a new breakthrough which is minimum tackifier with certain treatment could give better performance.